Implementasi Kurikulum 2013 pada Materi Permainan Bola Besar di SDN 1, 2, 3 Krajan Kecamatan Jatinom Kabupaten Klaten. - Mulyanto, Rinaldi Bayu; Sulaiman, Sulaiman (Universitas Negeri Semarang, 2023)
The purpose of this study is to find out how the implementation of the 2013 curriculum on large ball material in the process of planning, implementing, and assessing learning.this type of research is qualitatively discptive. The location of this study was 3 elementary schools in jatinom subdistrict of klaten district. The data sources in this study consisted of 3 health care teachers and 6 students. The instruments used in this study were observations, interviews, and documentation. Validity of data using Triangulation techniques. The data analysis used is data reduction, data presentation, and drawing conclusions. Based on the research conducted, it can be concluded that the Implementation of the 2013 Curriculum on Big Ball Game Materials at SDN 1, 2, 3 Krajan, Jatinom District, Klaten Regency is planning carried out by PJOK teachers who have implemented the 2013 curriculum by the teacher, learning based on the 2013 curriculum has been carried out by the teacher with a scientific approach, and the assessment process carried out is based on the lesson plans that have been prepared.